Sensemaking of Wisdom Pedagogy Research in Education - Maria Jakubik (International Journal of Management, Knowledge and Learning)
Purpose: This paper asks: How has wisdom pedagogy research evolved in education from 1980 to 2022 and what are its characteristics and its possible future trends?